Gender Budgeting as a Tool for Achieving Sustainable Development: A Future Vision for Iraqi Government Institutions - Raghad Hashem Al-Mallah; Abdulwahed Ghazi Mohamed (Indonesian Journal of Law and Economics Review, 2026)
General Background Public sector budgeting operates as a strategic fiscal instrument for promoting inclusive economic growth and distributive justice. Specific Background Within the Iraqi administrative environment, transitioning toward progressive financial frameworks is necessary to address diverse socioeconomic needs and promote equitable wealth distribution. Knowledge Gap However, government entities currently rely on conventional line-item budgeting systems that fail to track social outcomes, while existing empowerment units lack genuine fiscal and technical decision-making authority. Aims This study develops a forward-looking roadmap to operationalize Gender-Responsive Budgeting as an accounting mechanism to advance the 2030 Sustainable Development Goals within Iraqi entities. Results Based on a mixed-methods approach utilizing evaluation checklists from 157 professional informants, empirical findings reveal a severe deficit in technical readiness for progressive budget execution. The accounting codification dimension recorded the lowest mean score of 1.35, underscoring a heavy dependence on traditional ledgers that do not measure equality outcomes. Furthermore, current empowerment structures function merely as formalistic setups without regulatory power over resource allocation. Novelty The research uniquely proposes restructuring the Unified Chart of Accounts to integrate specific digital codes and mandating corresponding analytical statements within final annual financial reports. Implications Achieving digital integration between local accounting systems and the Integrated Financial Management Information System is imperative to ensure equitable resource allocation, organizational transparency, and robust fiscal accountability. Highlights: Empirical evaluations from 157 government professionals reveal a severe deficit in technical readiness for progressive fiscal execution. Existing accounting codification frameworks heavily rely on traditional line-item ledgers that fail to track social outcomes. Restructuring the Unified Chart of Accounts to include specific digital codes guarantees organizational transparency and resource accountability. Keywords: Gender-Responsive Budgeting, Accounting Codification, Sustainable Development Goals, Fiscal Accountability, Integrated Financial Management Information System